Impacts of a marine engineering project on hydrodynamics and diffusion characteristics of fluvial pollutants in Laizhou Bay, China - Wang, Zhanjin; Bao, Rui; Wang, Weizhong; Li, Wanhua; Leng, Xing; Liang, Jinhui; Zhang, Wei (Frontiers in Earth Science, 2024)
IntroductionThe rapid advances in marine engineering projects are exacerbating environmental pressures on bay ecosystems. This study utilized the MIKE 21 model to evaluate the impacts of such projects in Laizhou Bay (LZB) on hydrodynamic conditions and the spread of dissolved inorganic nitrogen (DIN) from riverine inputs.ResultsThe results indicated an expansion of 80.77 km2 in areas with DIN concentrations surpassing 0.5 mg/L 2 months after input from the Yellow River, with increased levels in the southern Yellow River Delta. Decreased flow velocities adjacent to the wave barriers at the Xiaoqing River estuary impeded lateral DIN dispersion, resulting in a 0.93 mg/L increase in DIN concentrations at the river mouth. After the construction of marine engineering projects (2020), significant alterations in the coastline of LZB have markedly modified hydrodynamic characteristics near marine structures, altering DIN dispersion patterns.ConclusionThis study provides crucial information for the management of pollutants at estuaries, understanding dispersion mechanisms, and evaluating the feasibility and environmental compatibility of marine engineering projects.